Pengaruh Latihan Circuit Training Terhadap Kondisi Fisik Atlet Dalam Olahraga Sepakbola Pada Klub PS Debai Kota Sungai Penuh - JONIKA TRISHANDRA; Mulza Rois (Jurnal Muara Olahraga, 2022)
This study aims to find information about the effect of circuit training on physical condition. This research is an experimental research conducted with the aim of knowing whether there is a consequence of something that is imposed on the sample to be studied. The research method used is the experimental method because it aims to see the consequences of a behavior. Experimental research is a way to find a cause-and-effect relationship between two factors that is intentionally caused by the researcher by reducing other disturbing factors. The number of samples of 15 people obtained from the total sampling technique. The study was conducted for 6 weeks, with 3 meetings per week. The instrument used to measure physical condition is the VO2Max test (Bleep test). The results of data analysis using the t-test showed a significant increase in the ability of physical conditions due to the influence of circuit training exercises (t-count 10.34 > t-table 1.76). Based on data analysis, it is known that t-count > t-table, it can be concluded that circuit training has an effect on the ability of physical conditions.